Use of Protein Content, Amylose Content, and RVA Parameters to Evaluate the Taste Quality of Rice - Shi, Shijie; Wang, Enting; Li, Chengxuan; Cai, Mingli; Cheng, Bo; Cao, Cougui; Jiang, Yang (Frontiers in Nutrition, 2022)
Taste quality of rice is the key to its value. However, it is greatly affected by rice types and the environment. It is complex but necessary work to accurately evaluate the taste quality of various types of rice in different environments. In this study, 7 different types of rice with different taste values were used as materials, and 12 nitrogen fertilizer treatments were applied to obtain 84 different rice taste values. We used protein content, amylose content, and RVA to evaluate the changes in the taste value of rice. Rice with high taste value tended to have higher amylose content, peak viscosity, hold viscosity, final viscosity, and breakdown, as well as lower protein content, pasting temperature, and peak time. Protein and amylose contents affected the taste value of rice by affecting the RVA profiles except for setback. For high and low taste values rice type, protein content could explain 66.8% and 42.9% of the variation of taste values, respectively. In the case of medium taste value type, the protein content was not enough to evaluate the taste quality of rice. The stickiness could explain 59.6% of the variation of taste values. When the protein content of rice was less than 6.61% or greater than 9.34%, it could be used to reflect the taste quality of rice. When the protein content was between the two, protein content was not enough to reflect the taste quality of rice. Our results suggested protein content could better reflect the taste quality change for rice, which provided a theoretical and technical basis for the accurate evaluation of the taste value of various types of rice.